The Geology of Stratigraphic Sequences - Miall, Andrew D. 1944- (Springer Berlin Heidelberg, 1997)
Sequence stratigraphy represents a new paradigm in geology. The principal hypothesis is that stratigraphie successions may be subdivided into discrete sequences bounded by widespread unconformities. There are two parts to this hypothesis. First, it suggests that the driving forces which generate sequences and their bounding unconformities also generate predietable three-dimensional stratigraphies. In re cent years stratigraphie research guided by sequence models has brought about fundamental im provements in our understanding of stratigraphie processes and the controls of basin architecture. Sequence models have provided a powerful framework for mapping and numerieal modeling, enabling the science of stratigraphy to advance with rapid strides. This research has demonstrated the importance of a wide range of processes for the generation of cyclie sequences, including eustasy, tectonics, and orbital forcing of climate change. The main objective of this book is to document the sequence record and to discuss our current state of knowledge about sequence-generating processes